Issues on the inclusion of Puntius denisonii (Day), a freshwater ornamental fish of global value, as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India - Jain, Atul Kumar; Mercy, T. V. A.; Jain, Abhinika (Frontiers in Marine Science, 2022)
Puntius denisonii is popularly known as Miss Kerala in India or Denison barb or Red line torpedo barb in the global ornamental fish trade. The species is endemic to fast-flowing rivers and streams of the Western Ghats of India. The species was not very popular earlier in aquatic trade but has been in great demand in global aquarium trade since it was exhibited at AQARAMA 1997 in Singapore and ranked third under the new species category. The export of the species from India started in 1996–1997, which increased progressively and constituted about 60%–65% of a total of 1.44 million US worth of ornamental fish exported from India in 2007–2008. Thereafter, it started declining and presently became negligible. It was attributed to depleting stocks of P. denisonii in rivers and streams of Western Ghats. The species was recommended to be listed as endangered on the IUCN red list in a CAMP workshop held at NBFGR, Lucknow, India in September 1997, owing to habitat degradation and the declining number of mature individuals in the wild. It was categorized as Vulnerable in 2009 and Endangered in 2015 under the IUCN red list. The Department of Fisheries, Government of Kerala has restricted the collection of smaller size fish from natural water bodies since 2008 to revive wild stocks. The Ministry of Environment, Forest and Climate Change, Government of India has now proposed to include P. denisonii along with two other freshwater fish species, Semiplotus semiplotus (Assamese kingfish) and Osteobrama belangeri (Manipur osteobrama), as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India. The species listed under this Schedule are prohibited to be hunted throughout the country. The captive breeding technology of P. denisonii has already been developed in the country more than a decade back, and fish is being produced commercially at several farms presently including hatcheries of the Kerala Government. The species is also being cultured and produced on a commercial scale by many ornamental fish farmers of Indonesia and supplied to the global ornamental fish trade at cheaper rates, and more color strains. The major factors that are responsible for the depletion of the stocks of P. denisonii and the overall fish biodiversity of Western Ghat regions are discussed in detail. The conflicts and repercussions that will arise because of the inclusion of Denison Barb or any other freshwater fish as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India are also discussed.